Willingness to pay for fish biodiversity preservation in the Smoky Hill river basin - Scheffler, Mary (Kansas State University, 2022)
The purpose of this thesis is to evaluate factors impacting residents' willingness to support local fish species preservation, through discovering how someone’s beliefs or values impact their commitment to pay for conservation efforts. The study gauges community members' willingness to support and pay for a policy for conservation efforts to preserve and restore native fish populations to local rivers and streams in the Smoky Hills River region in Central Kanas. In addition, the thesis examines factors, such as demographics, knowledge of local environmental issues, and various economic factors, to assess their impact on the decision to support the proposed policy. Data was obtained from a survey conducted by Kansas State University and distributed to residents of the Smoky Hill Basin area. The survey asked a variety of questions including: social economics, environmental engagement levels, and perceptions of conservation issues that may impact residents. Econometric regression analysis is then used to understand what level of support residents would potentially be willing to give to conservation efforts to restore local fish populations and which factors significantly influence residents' decisions to support the identified proposal. Policymakers and members of academia can use this research to further understand residents' motivations and which factors impact people’s support for environmental policy.
Keywords: Conservation; Aquaculture; Agribusiness; Environmental policy; Regression